Material removal rate and surface roughness study on Near-dry wire electrical discharge Machining process. (2021) - Boopathi, S.; Myilsamy, Sureshkumar
Abstract: In this article, the near-dry wire electrical discharge machining (NDWEDM) experiments were carried out with fixed values of pulse-off time, gap-voltage, the thickness of the materials, and wire-speed on the Material Removal Rate (MRR), and Surface Roughness (SR). AISI-D3 tool steel has been used to conduct the tests due to the increase of manufacturing applications of measuring tools, dies, and punches. NDWEDM of AISI-D3 tool steel was studied with the mixing of oxygen gas with water that has been used as the dielectric fluid. In this study: current, pulse on time, oxygen-mist pressure, and flow rate of mixing water are accounted to improve the machining characteristics. The rotatable central composite design (CCD) design of experiments was applied to perform and analyze the trials. The effects of NDWEDM parameters on MRR and SR have been analyzed by mathematical models and response surfaces.